Small animal deworming protocols, client education, and veterinarian perception of zoonotic parasites in western Canada - Stull, Jason W. (Canadian Veterinary Medical Association, 2007)
Questionnaires were mailed to veterinarians in western Canada to determine dog and cat deworming protocols and the association between perceived zoonotic risk and perceived prevalence of endoparasites and deworming protocols. Of the responding veterinarians (545), 13% and 39% recommended deworming protocols consistent with established guidelines for puppies and kittens, respectively. Mixed animal practitioners and high-perceived prevalence of Toxocara cati were associated with increased appropriate kitten deworming (P < 0.01 and P = 0.04, respectively). High-perceived zoonotic concern of Toxocara canis was associated with increased appropriate puppy deworming (P = 0.01). Sixty-eight percent of veterinarians noted an established hospital deworming protocol, although only 78% followed the protocol. Forty-four percent of veterinarians stated they discussed with all clients the zoonotic risk of animal-derived endoparasites, whereas the remainder discussed it only under particular circumstances or not at all. Most small animal deworming protocols recommended in western Canada begin too late to inhibit endoparasite shedding. Increased educational efforts directed at veterinarians are warranted.